PENGARUH STRUKTUR MODAL DAN PERUBAHAN LABA TERHADAP NILAI PERUSAHAAN PERDAGANGAN ECERAN DI BURSA EFEK INDONESIA - Vargo Christian Tobing (Universitas Pamulang, 2019)
The conduct of this research aims to see how the influence of capital structure and changes in earnings on firm value. The population in this study are retail trade sub-sector companies in the Indonesia Stock Exchange. Determination of the sample using purposive sampling method. The samples studied in this study were 9 companies. The results of the study concluded that the capital structure measured by the ratio of debt to equity ratio has no significant effect on firm value, earnings changes have no significant effect on firm value, and simultaneously, capital structure and earnings changes have no significant effect on firm value.